2011
DOI: 10.5603/fhc.2011.0022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of monocyte-derived dendritic cells, T regulatory and Th17 cells in chronic myeloid leukemia patients treated with tyrosine kinase inhibitors

Abstract: Abstract:Immunotherapy with dendritic cells (DC) may constitute a new and advantageous option for patients with chronic myeloid leukemia (CML) who respond to therapy with tyrosine kinase inhibitors (TKI), but do not reach complete cytogenetic or molecular remission. In this study, we evaluated the immunophenotype of DC generated from monocytes (Mo-DC) of patients with CML and the influence of TKI therapy on the results of CML-DC generation. We also measured the percentages of T regulatory cells (Tregs) as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…Therefore, our results show that CRC exerts negative effects on DC generation and maturation at a systemic level and that both of these deficiencies appear to correlate with the disease stage. These observations agree with those of previous studies on different tumor types [2022,24,47,48]. Conversely, Gabrilovich et al showed that DCs isolated from breast cancer patient blood samples are impaired with regard to phenotypic features and in vitro antigen presentation, whereas DCs generated in vitro from blood precursors in the same patient samples are totally functional; the authors concluded that defective DC function can be at least partially overcome by removing the tumor immunosuppressive factors and generating DCs in vitro [49].…”
Section: Resultssupporting
confidence: 94%
“…Therefore, our results show that CRC exerts negative effects on DC generation and maturation at a systemic level and that both of these deficiencies appear to correlate with the disease stage. These observations agree with those of previous studies on different tumor types [2022,24,47,48]. Conversely, Gabrilovich et al showed that DCs isolated from breast cancer patient blood samples are impaired with regard to phenotypic features and in vitro antigen presentation, whereas DCs generated in vitro from blood precursors in the same patient samples are totally functional; the authors concluded that defective DC function can be at least partially overcome by removing the tumor immunosuppressive factors and generating DCs in vitro [49].…”
Section: Resultssupporting
confidence: 94%
“…Since MDSCs drive the development of T-reg [21], [22], [34], in some patients we also investigated the levels of circulating T-reg cells. As it has been reported [35], [36], in CML patients T-reg resulted significantly increased in respect to HD and we found that they directly correlated with Gr-MDSCs. Similar to Gr-MDSCs, the percentage of T-reg cells decreased to the HD levels after TKI therapy, confirming the correlation with the amount of granulocytic MDSCs.…”
Section: Discussionsupporting
confidence: 84%
“…Rojas et al found a lower Treg number in patients who achieved a complete cytogenetic response [ 63 ], while higher Treg frequencies were found after stem cell transplant compared to normal controls and newly diagnosed patients [ 64 ]. Finally, the correlations with Sokal score and basophil number were validated by other studies [ 65 , 66 ], whereas the impact of treatment has not been confirmed, since no changes in Treg frequency was observed after 6 months of tyrosine kinase inhibitors therapy [ 65 ]. Table 5 summarizes the results of studies analyzing Tregs in CML.…”
Section: Regulatory T Cells In Acute Leukemias Chronic Myeloid Lementioning
confidence: 93%